2013
DOI: 10.1128/aem.01077-13
|View full text |Cite
|
Sign up to set email alerts
|

Functional Screening of Metagenome and Genome Libraries for Detection of Novel Flavonoid-Modifying Enzymes

Abstract: The functional detection of novel enzymes other than hydrolases from metagenomes is limited since only a very few reliable screening procedures are available that allow the rapid screening of large clone libraries. For the discovery of flavonoid-modifying enzymes in genome and metagenome clone libraries, we have developed a new screening system based on high-performance thin-layer chromatography (HPTLC). This metagenome extract thin-layer chromatography analysis (META) allows the rapid detection of glycosyltra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 70 publications
(25 citation statements)
references
References 73 publications
0
25
0
Order By: Relevance
“…To date, no thermolabile APs from metagenomes have been isolated or characterized. This might be due to the limited availability of sensitive and reliable screening systems, which enable the screening of large libraries of metagenome clones [ 17 , 18 ]. Recently, we developed a genetic circuit termed the Genetic Enzyme Screening System (GESS) that allows for the measurement of enzyme activity as in vivo fluorescence intensity and is highly useful for high-throughput metagenomic screening of enzymes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…To date, no thermolabile APs from metagenomes have been isolated or characterized. This might be due to the limited availability of sensitive and reliable screening systems, which enable the screening of large libraries of metagenome clones [ 17 , 18 ]. Recently, we developed a genetic circuit termed the Genetic Enzyme Screening System (GESS) that allows for the measurement of enzyme activity as in vivo fluorescence intensity and is highly useful for high-throughput metagenomic screening of enzymes [ 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…For more than a decade, metagenome research has demonstrated that it is a powerful tool for the discovery of novel biocatalysts and other valuable biomolecules by using either function or sequence-based screening technologies, addition to its impact on bacterial biodiversity. Sequence-based approaches allow the identification of candidate genes [24]. In the last years were studies initiated to investigate the metagenome [13].…”
Section: Discussionmentioning
confidence: 99%
“…Other approaches and techniques that have been successfully utilized for fine-tuning gene expression for the needs of metabolic engineering were thoroughly reviewed in [192]. Furthermore, a new screening technique based on high-performance thin-layer chromatography (HPTLC) has been developed for the discovery of flavonoid-modifying enzymes [193]. The authors claim that this metagenome extract thin-layer chromatography analysis (META) allows rapid detection of glycosyltransferases and other flavonoid-decorating enzymes, as well as that the system is highly sensitive, being able to detect of as little as 4 ng of a modified molecule.…”
Section: Strategies For Improving Production Of Polyphenolic Compoundmentioning
confidence: 99%